2004
DOI: 10.1143/ptp.111.463
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization Analysis of Resonance Structure in a 2-D Symplectic Map

Abstract: A symplecticity-preserving RG analysis is carried out to study a resonance structure near an elliptic fixed point of a proto-type symplectic map in two dimensions. Through analyzing fixed points of a reduced RG map, a topology of the resonance structure such as a chain of resonant islands can be determined analytically. An application of this analysis to the Hénon map is also presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Since this direct method is a discrete version of the perturbative renormalization group method for a flow system [5], we call it the renormalization method or the R method here. In the paper [2], it was predicted and confirmed that the island structures appear due to the PB resonance near some rational tori.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Since this direct method is a discrete version of the perturbative renormalization group method for a flow system [5], we call it the renormalization method or the R method here. In the paper [2], it was predicted and confirmed that the island structures appear due to the PB resonance near some rational tori.…”
Section: Introductionmentioning
confidence: 76%
“…(4) takes the form of the double-well type map [4,7]. Some resonant structures of these two maps were studied near the elliptic fixed point by means of the renormalization method [2]. Here, we investigate the map (4) in the more general setting, taking note of the fact that the map (4) includes the integral map of the Suris' type [8].…”
Section: Symplectic Map Near Elliptic Fixed Pointmentioning
confidence: 99%
See 3 more Smart Citations